Spontaneous coronary artery dissection in women in the generative period: clinical characteristics, treatment, and outcome—a systematic review and meta-analysis - Apostolović, Svetlana; Ignjatović, Aleksandra; Stanojević, Dragana; Radojković, Danijela Djordjević; Nikolić, Miroslav; Milošević, Jelena; Filipović, Tamara; Kostić, Katarina; Miljković, Ivana; Djoković, Aleksandra; Krljanac, Gordana; Mehmedbegović, Zlatko; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Spontaneous coronary artery dissection (SCAD) is a non-traumatic and non-iatrogenic separation of the coronary arterial wall.This systematic review and meta-analysis is reported following the PRISMA guidelines and is registered in the PROSPERO database. A literature search was focused on female patients in generative period (16-55 of age) with acute coronary syndrome (ACS) caused by SCAD, and comparison from that database NP-SCAD (spontaneous coronary artery dissection in Non Pregnant women) and P-SCAD (spontaneous coronary artery dissection in Pregnant women).Results: 14 studies with 2145 females in the generative period with ACS caused by SCAD were analyzed. The median age was 41 years (33.4 -52.3 years). The most common risk factor was previous smoking history in 24.9% cases. The most common clinical presentation of ACS was STEMI in 47.4%. Conservative treatment was reported in 41.1%. PCI was performed in 32.7%, and 3.8% of patients had CABG surgery. LAD was the most frequently affected (50.5%). The prevalence of composite clinical outcomes including mortality, non-fatal MI and recurrent SCAD was 3.3% (95% CI 1.4-5.1), 37.7% (95% CI 1.9-73.4) and 15.2% (95% CI 9.1-21.3) of patients. P-SCAD This is a provisional file, not the final typeset article compared to NP-SCAD patients had more frequently STEMI (OR=3.16; 95% CI: 2.30 -4.34; I2=64%); with the left main and LAD more frequently affected [(OR=14.34;; I 2 =54%) and (OR=1.57; 95% CI: 1.06-2.32; I 2 =23%)]; P-SCAD patients more frequently underwent CABG surgery (OR=6.29; 95% CI: 4.08-9.70; I 2 =0%). NP-SCAD compared to P-SCAD patients were more frequently treated conservatevly (OR=0.61; 95% CI: 0.37-0.98; I 2 =0%). In P-SCAD compared to NP-SCAD mortality rates (OR=1.13; 95% CI: 0.06-21.16; I 2 =not applicable) and reccurence of coronary artery dissection (OR=2.54; 95% CI: 0.97-6.61; I 2 =0%) were not more prevalent.The results of this meta-analysis indicated that patients with P-SCAD had more frequently STEMI, and more frequently involved left main and LAD compared to NP-SCAD patients. Women with NP-SCAD were significantly more often treated conservatively compared to P-SCAD patients. P-SCAD compared to NP-SCAD patients did not have significantly higher mortality rates or recurrent coronary dissection.